2016
DOI: 10.1128/aem.02518-15
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Profile of Chinese Liquor Is Altered by Interactions of Intrinsic and Extrinsic Microbes

Abstract: The flavor profile of Chinese liquor is the result of the metabolic activity of its microbial community. Given the importance of the microbial interaction, a novel way to control the liquor's flavor is by regulating the composition of the community. In this study, we efficiently improved the liquor's flavor by perturbing the intrinsic microbial metabolism with extrinsic microbes. We first constructed a basic microbial group (intrinsic) containing Saccharomyces cerevisiae, Wickerhamomyces anomalus, and Issatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…The supernatant was diluted in a gradient and plate spread. Four kinds of yeast enumeration methods were carried out on Wallerstein laboratory nutrient (WLN) medium (77), in which the strains showed different macroscopic features (texture, surface, margin, and color).…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant was diluted in a gradient and plate spread. Four kinds of yeast enumeration methods were carried out on Wallerstein laboratory nutrient (WLN) medium (77), in which the strains showed different macroscopic features (texture, surface, margin, and color).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, although the 24 yeast strains were comparable in solid state fermentation, more alcohol was produced via SSF, with an average yield of 8.4 g/100 g for SSF vs. 3.7 g/100 g by SMF. Other studies have also confirmed that SSF is more suitable for ethanol production . In addition, flavour metabolites were different in liquid‐ and solid state cultures, with esters mostly found in SSF, while more higher alcohols were formed in the SMF process .…”
Section: The Contribution Of Yeast To Flavours and Aromasmentioning
confidence: 75%
“…Correlation analysis showed that, in a mixed culture system, the increase in ethyl hexanoate, isobutanol and 3‐methylbutyric acid could be related to the increased growth of S. cerevisiae and P. kudriavzevii ; however, the decrease in geranyl acetone was correlated with the reduced growth of P. anomalus . The amount of phenylethanol in all of the cocultures was lower than that in a single culture, which is beneficial to the flavour balance, as overproduction of a single metabolite can lead to a liquor with distorted flavour .…”
Section: Interactions Between Yeast and Other Microorganisms In Mixedmentioning
confidence: 90%
See 1 more Smart Citation
“…The addition of extrinsic microbes changed the growth and flavour metabolism of the intrinsic microorganisms, which indicated the possibility of regulating the fermentation process using extrinsic Table 2. Microbial communities of fermented grains by polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) and small-subunit rRNA (SSU rRNA) microbial groups (47). The improvement and refinement of this technology would be beneficial for maintaining the stability of products among batches and also improve the quality of Chinese Baijius.…”
Section: Fermentation Process Regulationmentioning
confidence: 99%